2016
DOI: 10.12659/msm.898593
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Genotoxic Effects of Hookah Smoking by Micronucleus and Chromosome Aberration Methods

Abstract: BackgroundUse of a hookah (a type of water pipe) is a traditional way of smoking tobacco, particularly in the Middle East. In Turkey, its popularity has been growing in recent years, especially among young people. It is known that cigarette smoking has genotoxic effects and causes mutations, but no comprehensive study has been done on the genotoxic effects of hookah usage, particularly in Turkey.Material/MethodsWe collected peripheral blood/buccal smear samples from 30 subjects who did not smoke cigarettes but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…The study showed that the mean number of micronuclei in buccal mucosa cells of waterpipe smokers was significantly higher than non-smokers. The genotoxic effect of waterpipe on buccal cells and peripheral blood leukocytes have been demonstrated with comet assay (13), sister chromatid exchanges (SCEs) assay (14) and chromosome analyses (15). In present study, using a simpler method, the previous results were confirmed.…”
Section: Discussionsupporting
confidence: 74%
“…The study showed that the mean number of micronuclei in buccal mucosa cells of waterpipe smokers was significantly higher than non-smokers. The genotoxic effect of waterpipe on buccal cells and peripheral blood leukocytes have been demonstrated with comet assay (13), sister chromatid exchanges (SCEs) assay (14) and chromosome analyses (15). In present study, using a simpler method, the previous results were confirmed.…”
Section: Discussionsupporting
confidence: 74%
“…The selected groups were age and sex matched. The sample size was determined according to similar studies [9, 10]. We included a relatively proportionate population of all three groups of light, moderate, and heavy smokers.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects who had smoked for at least 1 year and reported smoking at least 5 cigarettes per day were considered cigarette smokers [11]. Individuals who had smoked waterpipe for at least 1 year and reported smoking waterpipe at least once per week were considered waterpipe smokers [10, 12]. Subjects who had never previously smoked either waterpipe or cigarettes were considered nonsmokers [10, 12].…”
Section: Methodsmentioning
confidence: 99%
“…A variety of factors including cigarette smoke can change the impact of genotoxic agents on the micronucleus frequency (Luzhna, Kathiria, & Kovalchuk, ). Exposure to cigarette smoke and hookah lead to increased micronucleus frequency (Cavalcante et al, ; Derici Eker et al, ). Several mechanisms have been proposed to explain micronuclei formation.…”
Section: Cigarette Smoking and Genetic Alterationsmentioning
confidence: 99%